2001
DOI: 10.1152/ajpheart.2001.281.4.h1532
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent modulation of cardiac calcium current by intracellular free magnesium

Abstract: We compared the effects of cytosolic free magnesium (Mg(2+)(i)) on L-type Ca(2+) current (I(Ca,L)) in patch-clamped guinea pig ventricular cardiomyocytes under basal conditions, after inhibition of protein phosphorylation, and after stimulation of cAMP-mediated phosphorylation. Basal I(Ca,L) density displayed a bimodal dependence on the concentration of Mg(2+)(i) ([Mg(2+)](i); 10(-6)-10(-2) M), which changed significantly as cell dialysis progressed due to a pronounced and long-lasting rundown of I(Ca,L) in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 33 publications
4
37
2
Order By: Relevance
“…In any case, the affinity of Mg 2+ for the low affinity site in the L-type channel permeation pathway would seem to indicate that the highest [Mg 2+ ] i used in the present study, 1.8 mM, would not have a significant effect on ion permeation. Nonetheless, given the assumptions and extrapolations needed to arrive at this conclusion, it is important to experimentally test whether [Mg 2+ ] i could be blocking ion permeation under the conditions of our experiments [3,4], that are similar to those of other reports in which [Mg 2+ ] i has been reported to decrease whole-cell Ca 2+ currents [1,5,22,23,25].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In any case, the affinity of Mg 2+ for the low affinity site in the L-type channel permeation pathway would seem to indicate that the highest [Mg 2+ ] i used in the present study, 1.8 mM, would not have a significant effect on ion permeation. Nonetheless, given the assumptions and extrapolations needed to arrive at this conclusion, it is important to experimentally test whether [Mg 2+ ] i could be blocking ion permeation under the conditions of our experiments [3,4], that are similar to those of other reports in which [Mg 2+ ] i has been reported to decrease whole-cell Ca 2+ currents [1,5,22,23,25].…”
Section: Discussionsupporting
confidence: 54%
“…This finding could be consistent with Mg 2+ acting as an open channel blocker. The findings of White & Hartzell [1] and Pelzer et al [25] that channel phosphorylation promotes the reduction of Ca 2+ current by cytosolic Mg 2+ current might also be consistent with Mg 2+ block of ion permeation through the open channel. This possibility motivated the present experiments to determine if [Mg 2+ ] i used here could decrease current in a manner consistent with permeation block.…”
Section: Discussionmentioning
confidence: 60%
“…This modulation does not necessarily involve changes in channel phosphorylation per se, but more generally appears to depend on the kinetics of gating induced by channel phosphorylation. (1,18,31,(41)(42)(43). Our recent study (37) also showed large changes in I Ca around physiologically relevant [Mg 2ϩ ] i .…”
mentioning
confidence: 70%
“…[Mg 2ϩ ] i could affect the level of channel phosphorylation by altering the activity of Mg 2ϩ -dependent kinases and phosphatases, and it could also modulate the effect of channel phosphorylation on gating kinetics. Previous studies (31) have shown that the former mechanism is possible. In addition, the latter has been discussed as an explanation for the results of Yamaoka and Seyama (44); however, direct experimental support for this mechanism is lacking. ]…”
mentioning
confidence: 85%
See 1 more Smart Citation